Metastatic Eccrine Carcinoma of The Axilla - A Case Report - Ray, Deepak Shankar; Chakraborty, Bhaskar; Sharif, Md Mofazzal; Hai, MA (KYAMC Journal, 2019)
Sweat gland carcinoma is very rare with a reported incidence of less than 0.005% of all tumour specimens resected surgically. These are considered as a rare group of tumours with potential for local destruction as well as distant metastasis. Wide surgical excision along with regional lymph node dissection in the presence of clinically positive nodes is the recommended treatment. However, the variability of the histological features even in the same tumour, and its rarity, have contributed to some confusion regarding the classification of sweat gland carcinoma as well as the treatment of specific histological subtypes. Apart from that, documentation is also inadequate regarding management of metastatic cases. Here we present a rare case of metastatic eccrine sweat gland carcinoma in a 50 year old male patient which initially created a diagnostic dilemma and was non responsive to different chemotherapies with gradual disease progression. KYAMC Journal Vol. 10, No.-2, July 2019, Page 114-117